2018
DOI: 10.2169/internalmedicine.0316-17
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Findings of Subclinical Influenza-associated Cardiac Abnormalities among Japanese Patients

Abstract: Objective Although life-threatening cardiac complications in influenza infection are rare, subclinical influenza-associated cardiac abnormalities may occur more frequently. We investigated the prevalence of subclinical cardiac findings. Methods After obtaining their written informed consent, 102 subjects were enrolled in the present study. The study subjects underwent a first set of examinations, which included electrocardiography (ECG), echocardiography, and the measurement of their cardiac enzyme levels. Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The present study was based on the data on our previous study [16], and thus was consistent with that study with respect to patient enrollment and study protocol. In the previous study, subjects recovering from IVI who presented 1 or more abnormal findings during the first assessment (electrocardiography for ST-T abnormalities, any arrhythmias, and others; echocardiography for reduced LV ejection fraction, diastolic dysfunction, and pericardial effusion; and elevated cardiac markers, namely, CKMB and/or cardiac troponin T) were advised to undergo a second set of assessment [16]. Clinical, echocardiographic, and biological characteristics at the initial set of examinations in patients who had any of the aforementioned abnormalities (n = 24) and in those who did not (n = 86) (4 excluded because of insufficient data acquisition) are presented in S1 Table, and how the 20 subjects were selected is shown in Fig 1.…”
Section: Methodssupporting
confidence: 53%
“…The present study was based on the data on our previous study [16], and thus was consistent with that study with respect to patient enrollment and study protocol. In the previous study, subjects recovering from IVI who presented 1 or more abnormal findings during the first assessment (electrocardiography for ST-T abnormalities, any arrhythmias, and others; echocardiography for reduced LV ejection fraction, diastolic dysfunction, and pericardial effusion; and elevated cardiac markers, namely, CKMB and/or cardiac troponin T) were advised to undergo a second set of assessment [16]. Clinical, echocardiographic, and biological characteristics at the initial set of examinations in patients who had any of the aforementioned abnormalities (n = 24) and in those who did not (n = 86) (4 excluded because of insufficient data acquisition) are presented in S1 Table, and how the 20 subjects were selected is shown in Fig 1.…”
Section: Methodssupporting
confidence: 53%
“…In a study of 75 inpatients with SARS, acute myocardial infarction was the cause of 2 of 5 deaths [40]. Elevated TnI levels are also common in infections caused by other influenza virus subtypes [41][42][43][44][45]. TnI may play an important role in predicting the acute or long-term risk of influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [13] , [14] , [15] , [24] have previously evaluated the impact of influenza viral infection on cardiac function and immediate mortality but only limited studies have determined the long term clinical consequences of severe influenza infection who require hospitalisation. These studies have indicated an increased incidence of arrhythmias, presence of regional wall motion abnormalities and a reduction in ejection fraction along with increased mortality during acute phase of viral illness.…”
Section: Discussionmentioning
confidence: 99%